PS-027 Effectiveness of an educational programme to promote a pharmacovigilance system. (14th February 2016) - Canadell, L; Olona, M; Martín, M; López, PA; De dios, A; Torrent, J; Sánchez, L; Berrueta, A; Rodríguez, E; Canela, M
Abstract : Background: Spontaneous reporting is an important tool for the surveillance of problems related to drugs (PRDs). However, under reporting is a major limitation of any pharmacovigilance system. In 2014 a new electronic tool (TPSCCloud) was established to notify patient events related to hospital assistance and those related to drugs. The pharmacy department is usually involved in providing information, recording PRDs and promoting a culture of safety and security. On this occasion, the pharmacy department supported diffusion of this programme in cooperation with the preventive service. Purpose: To measure the effectiveness of an educational programme implemented in 2014 to increase the reporting of medication events. Also, notifications were evaluated for a period of 1 year in terms of: number of notifications, characteristics, and nature and severity of the reports, and compared with the last period (2013). Material and methods: Spontaneous reporting of PRDs by healthcare professionals is a longstanding limitation. The development of educational programmes for healthcare professionals has the potential to enhance participation in pharmacovigilance. The pharmacy department established sessions focused on explaining the pharmacovigilance programme in the hospital and practical instructions to access and report the events in the electronic system. We focused our efforts on doctors who usually provide fewer voluntary reports of events and medication errors. Results: 22 pharmacovigilance sessions were done in 2014. Notifications of PRD increased by 140%, from 64 in 2013 to 154 in 2014. Notifications of drug errors increased by 85%, from 48 to 89. 3 drug classes were frequently involved: antibiotics, cytostatics and analgesics, in both periods. The events that directly affected patients were similar (84% in 2013 and 88.5% in 2013). The PRD reported differed in severity: 'no harm' from 25% in 2013 to 40% in 2014, 'monitoring was required' from 11% to 15%, 'intervention required or temporal harm' from 18% to 12% and 'high severity' (prolonged hospitalisation or permanent lesion) from 31.25% to 19% in 2014. Doctor/pharmacist notifications increased from 53% to 67%. Conclusion: Communication and educational programmes should be implemented to promote detection, identification, reporting and evaluation of PRMs. No conflict of interest.